Reanimação cardiopulmonar: habilidades afetivas da equipe de enfermagem em terapia intensiva - Patricia Sarsur Nasser Santiago (2006)
Skills needed for any professional activity, especially among health care staff, are not limited to the domain of knowledge (cognitive abilities), or even to motor abilities (psychomotor). It needs affective skills too, since values and feelings are of fundamental importance. The importance of affective skills in the nursing education is evident because of their proximity to patients and their families while providing care. In the present study I sought to analyze affective skills of the nursing staff of an Intensive Care Unit (ICU), during Cardiopulmonary Reanimation (CPR), based on the theoretical approach of Benjamim Bloom and colleagues. The research was accomplished in an ICU of a large hospital of Belo Horizonte. The sample was composed of 59 nurses, which corresponds to 70,2% of the studied population. Eighteen (30,5%) are nurse auxiliary, 27 (45,8%) are nurse technicians and 14 (23,8%) are registerednurses. Most of participants (n = 37; 91,5%) are female, and 71,2 percent said they are Roman Catholic. Thirty seven (62,7%), were from 20 to 39 years of age, and 45 (76,5%) were graduated in the last 10 years. Half of the sample (n = 30; 50,9%) were high school graduated, and 37 (62,7%) had up to 5 years of working experience in an ICU. Bloom´s five categories of affective skills indicated that: 94,9% manifested perception of the phenomenon (reception); 98,3% showed disposition to work with CPR (disposition on their answer). However only 20,3% demonstrated satisfaction in participating on the procedure (satisfaction on theiranswer). In the valorization category, most of the sample had values for a CPR. In relation to value organization, nurses´technical skills was rated higher in importance. Among the factors that influenced affective skills, the most cited items were: work team, material resources,human resources, psychological aspects, faith, and others. It is expected that this study may provide additional understanding of ICU nurses´ behavior, who work in cardiopulmonary reanimation, contributing to the development and improvement of their affective skills.